Smoking-related knowledge and attitudes of senior Australian medical students. Issue 4 (1996) - Roche, A M; Eccleston, P; Jordan, D
Abstract : OBJECTIVE: To assess the smoking-related knowledge and attitudes of senior medical students and to compare knowledge and attitude changes in students exposed to four different smoking cessation skills training interventions. DESIGN: A survey questionnaire, assessing knowledge and attitudes, was administered pre- and post-intervention for each of the four intervention conditions. SUBJECTS: A cohort of 219 fifth-year medical students at the University of Sydney. INTERVENTIONS: Students were randomised into one of four intervention conditions: (1) a traditional didactic lecture mode (control group); (2) the use of role plays and audiotaped feedback; (3) role plays with peer feedback; and (4) video feedback. MAIN OUTCOME MEASURES: Knowledge on morbidity and mortality associated with smoking, intervention strategies, intervention effectiveness, and cessation practices; anticipated clinical behaviour related to smoking; and attitudes towards medical practitioner involvement in smoking cessation. RESULTS: Smoking knowledge was significantly greater at post-test (mean unweighted scores of 69% before and 74% after intervention). All groups had improved knowledge levels at post-test. However, after controlling for pre-test differences, the control group, video feedback, and peer feedback groups were found to have improved significantly over the audio feedback group. Scores were higher on items related to morbidity and mortality and intervention effectiveness than for items on intervention strategies and cessation practices. Positive student attitudes towards their role in smoking cessation were also found. There was an almost universally held view that doctors can have a significant impact on reducing smoking levels. Although most students perceived smoking intervention to be a worthwhile activity, they remained pessimistic about the ease with which patients' smoking behaviour could be changed. CONCLUSIONS: Positive smoking cessation knowledge changes can be readily achieved through training. However, specific smoking cessation training is needed for medical trainees to develop appropriate skills and strategies. Attention to particular weaknesses related to specific intervention strategies and cessation practices is required to develop competence in this area and to maximise the chances of new medical graduates fully using the opportunities available to them.